The Plague of Justinian: Political, Economic and Societal Impacts - Ikican, Bahadır (Fırat University, 2023)
In 541 AD, the plague which broke out in Egyptian city of Pelesium which was called as a corn loft of the Byzantine Empire, and directy or indirectly affected through all the coastal cities of Mediterranean. The plague which was felt its effect for nearly two centuries, spread to the inner regions over time and made its presence felt in many parts of Europe. The plague, which initially spread by means of the trade, also spread to various places through missionaries who preached Christianity especially in Britain. The causes of the plague, which emerged in sixth century, were not only biological factors but also a number of climate crises. The volcanic winter, which is thought to have affected the northern hemisphere in 536, was important in the emergence of the plague and the increase in the number of people who lost their lives during the epidemic. According to current research, the climate crisis caused by a volcanic eruption or a comet impact on the earth’s surface has created a decline in agricultural production. Most of the farmers who could not get enough goods due to the volcanic winter that lasted for two years, had to migrate to meet their needs. The migration movement not only caused the abandonment of agricultural areas, but also made it difficult for the people of Late Antiquity, who were already unable to achieve adequate and balanced nutrition, to meet their consumption needs. As a matter of fact, this situation caused people’s immune system to decrease significantly in the face of the epidemic. In this context, although the 536 climate crisis was not the primary cause of the plague, it was an important element in the spread of the epidemic and the increase in death rates. The plague deeply affected the Byzantine Empire, which was based on permanent settlement. In addition to the plague costing the lives of many people, the fact that healthy people left their homes for the fear of contractiong the disease gave rise to the migration movement. This migration has created a great problem in terms of increasing public order and providing food. Moreover, the very high death rates caused by the plague made it difficult to find people to work in agriculture and various jobs, and this caused an increase in labor prices. Iustinianus, the Byzantine Emperor of the period, also anacted laws to prevent these price increases. In addition, the high human lost caused difficulties in recruiting soldiers to the army, and the empire had to turn to “barbarian” mercenaries. The fact that the plague, which affected almost all Mediterranean cities, spread especially to the inner parts of Europe is a very important element for the medieval European World. The people who avoided catching the plague turned to religion, which enabled the church to increase its power, and the adoption of the idea of a self-sufficient economy by minimizing the connection with the outside World was an important factor in the formation of the feodal social order.

Bizans İmparatorluğu’nun “tahıl ambarı” olarak adlandırılan Mısır’ın Pelusium kentinde 541’de patlak veren veba salgını, doğrudan ya da dolaylı yoldan Akdeniz’in tüm sahil kentlerini etkilemiştir. Yaklaşık iki yüzyıl boyunca etkisini hissettiren veba salgını, zamanla iç bölgelere de sirayet ederek Avrupa’nın pek çok bölgesinde varlığını hissettirmiştir. Başlangıçta ticaret vasıtasıyla yayılım gösteren salgın, bilhassa Britanya’da Hıristiyanlığı tebliğ eden misyonerler aracılığıyla muhtelif yerlere de yayılmıştır. Altıncı yüzyılda ortaya çıkan veba salgının arkasında sadece biyolojik etmenlerin değil, aynı zamanda birtakım iklimsel krizlerin de yattığı düşünülmektedir. Bilhassa 536’da Kuzey Yarım Küre’yi etkilediği düşünülen volkanik kış, veba salgının ortaya çıkışında ve salgın sırasında yaşamını yitiren insan sayısının artışında önemli bir etkendir. Güncel araştırmalara göre bir volkan patlaması ya da dünya yüzeyine bir kuyruklu yıldız çarpması sonucu ortaya çıkan iklim krizi, tarımsal üretimde bir düşüş yaratmıştır. Yaklaşık iki yıl kadar süren volkanik kış nedeniyle yeterli ürün elde edemeyen çiftçilerin büyük bir kısmı ihtiyaçlarını karşılamak amacıyla göç etmek durumunda kalmışlardır. Yaşanan bu göç hareketi, sadece tarım arazilerinin boş kalmasına neden olmamış, aynı zamanda zaten yeterli beslenme konusunda pek de başarılı olamayan Geç Antik Çağ insanlarının tüketim ihtiyaçlarına ulaşımını zorlaştırmıştır. Nitekim bu durum da insanların salgın karşısında bağışıklık sistemlerinin iyiden iyiye düşmesine sebep olmuştur. Bu bağlamda 536 iklim krizi, vebanın birincil etkeni değilse de salgının yayılımında ve ölüm oranlarının artmasında önemli bir unsurdur. Veba salgını bilhassa yerleşik düzen üzerine kurulu olan Bizans İmparatorluğu’nu derinden etkilemiştir. Salgının pek çok insanın canına mal olmasının yanında sağlıklı insanların hastalığa yakalanmaktan korkarak bulundukları yerleri terk etmeleri, bir göç hareketi doğurmuştur. Yaşanan bu göç hareketi de asayişsizliğin artması ve iaşe teminin sağlanması noktasında büyük bir sıkıntı yaratmıştır. Dahası salgın kaynaklı ölüm oranlarının oldukça yüksek olması, tarımda ve muhtelif işlerde çalışacak insan bulmayı zorlaştırmış ve bu durum da işgücü fiyatlarında artışa neden olmuştur. Dönemin Bizans İmparatoru Iustinianus da bu fiyat artışlarının önüne geçmek için yasalar çıkarmıştır. Ayrıca insan kaybının fazla olması orduya asker alımında sıkıntı çıkarmış ve imparatorluk “barbar” paralı askerlere yönelmek durumunda kalmıştır. Hemen hemen tüm Akdeniz kentlerini etkisi altına alan veba salgının özellikle Avrupa’nın iç kesimlerine yayılım göstermesi, Orta Çağ Avrupa dünyası açısından oldukça önemli bir unsurdur. Vebaya yakalanmaktan imtina eden insanların dine yönelmesi, kilisenin gücünü arttırmasını sağlamıştır. Ayrıca dış dünyayla bağlantının en aza indirilerek kendi kendine yeten bir ekonomi fikrinin benimsenmesi, feodal düzenin oluşumu noktasında önemli bir etken olmuştur.
IUSTINIANUS VEBASI: SİYASİ, EKONOMİK VE SOSYAL ETKİLERİ
Keywords: Intellectual History of Politics; Siyasi Düşünce Tarihi